Innovation and exports of German business services enterprises: First evidence from a new type of firm data - Alexander Vogel; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This paper contributes to the literature by providing the first evidence on the link between innovation activities (measured by the share of engineers and scientists in the workforce) and exports of German business services firms based on a large representative longitudinal sample of enterprises. The data combine for the first time information at the firm-level that is taken from data produced by the Statistical Offices and by the Federal Labour Agency. We document that R&D activities are positively linked with exports, and that this link is present when observed firm characteristics (including firm size, productivity, and human capital intensity) and unobserved time-invariant firm characteristics are controlled for. From an economical point of view the effect is, however, rather small. Furthermore, we find some evidence for self-selection of innovative services firms on export markets. We have to admit, however, that the panel is too short, and that the number of firms that start to export and start to perform R&D during the period under investigation is too small, for any convincing attempt to investigate the direction of the causal link between exports and innovation activities.
Keywords: F14; 330; Innovation; export; business services; Germany; Unternehmensdienstleistung; Innovation; Forschung; Internationaler Dienstleistungsverkehr; Export; Deutschland